2001
DOI: 10.1002/ajmg.10153
|View full text |Cite
|
Sign up to set email alerts
|

Genomic screen and follow‐up analysis for autistic disorder

Abstract: Autistic disorder (AutD) is a neurodevelopmental disorder characterized by significant impairment in social, communicative, and behavioral functioning. A genetic basis for AutD is well established with as many as 10 genes postulated to contribute to its underlying etiology. We have completed a genomic screen and follow‐up analysis to identify potential AutD susceptibility loci. In stage one of the genome screen, 52 multiplex families (two or more AutD affected individuals/family) were genotyped with 352 geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
171
1
40

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 263 publications
(193 citation statements)
references
References 51 publications
10
171
1
40
Order By: Relevance
“…The location of this signal overlaps with positive results from analysis from the International Molecular Genetic Study of Autism Consortium (IMGSAC) 16,17,25 and from others. 15,19,23 Thus, our data provides strong support for an autism locus on chromosome 7, both as an individual result, and in conjunction with previous results. Notably missing from our genome scan were signals corresponding to those reported by others on chromosome 2 13,16,17,23,45 and chromosome 17.…”
Section: Primary Genome Scansupporting
confidence: 88%
See 4 more Smart Citations
“…The location of this signal overlaps with positive results from analysis from the International Molecular Genetic Study of Autism Consortium (IMGSAC) 16,17,25 and from others. 15,19,23 Thus, our data provides strong support for an autism locus on chromosome 7, both as an individual result, and in conjunction with previous results. Notably missing from our genome scan were signals corresponding to those reported by others on chromosome 2 13,16,17,23,45 and chromosome 17.…”
Section: Primary Genome Scansupporting
confidence: 88%
“…15,19,23 Thus, our data provides strong support for an autism locus on chromosome 7, both as an individual result, and in conjunction with previous results. Notably missing from our genome scan were signals corresponding to those reported by others on chromosome 2 13,16,17,23,45 and chromosome 17. 14,20,24 Gender and linkage analyses Previous work by others suggested that linkage signals on chromosomes 4, 14,20 7, 17 and 17 14,20 were dependent on the gender of the affected individuals in the families.…”
Section: Primary Genome Scansupporting
confidence: 88%
See 3 more Smart Citations